Strategy for Teacher Professionalism Development in Improving the Quality of Learning at MIN 45 Pidie - Nanda Saputra; Khaidir Khaidir; Miswar Saputra (Program Studi Magister Manajemen Pendidikan)
Abstract: Strategy for Teacher Professionalism Development in Improving the Quality of Learning at MIN 45 Pidie. Professionalization in the field of teacher training means increasing all the power and effort in order to achieve optimal services that will be provided to the community. To improve the quality of education today, the professionalization of teachers is a must. The development of teacher professionalism is intended to stimulate, maintain, and improve teacher competence in solving education and learning problems that have an impact on improving the quality of student learning outcomes. Professionalism itself can mean the quality, quality, and behavior which are the characteristics of a profession or professional person. The purpose of this research is to describe the success of a teacher in madrasah, which is expected to have an influence on the quality of the madrasah. It is hoped that the professionalism of a teacher will help the development of madrasas. This research is a field research which is used as a descriptive qualitative research. This qualitative research is carried out by reducing data, presenting data and concluding / verification. Data collection methods in this research are interviews, observation, and documentation. The results of this research show that the efforts of madrasah principals to improve teacher professionalism, good coordination link all teaching staff in madrasas which are the basis for improving teacher professionalism, pedagogical competence, professional competence, character competence and social competence. Keywords: strategy, development, professionalism, teacherDOI: 10.23960/jmmp .v9.i1.2021